2017
DOI: 10.1002/cncr.30781
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of different subtypes of nasopharyngeal carcinoma reveals similarities and differences to guide targeted therapy

Abstract: These results indicate that different NPC subtypes harbor different CRGAs. Both EBV infections and the TMB are associated with the NPC subtypes as well as the alterations of individual genes and pathways. The high frequency of IDH2 mutations in NPUC may facilitate potential targeted therapy and will ultimately point to new therapeutic strategies. Cancer 2017;123:3628-37. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
(91 reference statements)
1
40
0
Order By: Relevance
“…1 These are thoughtful queries that must be addressed around the classification of tumors. 1 These are thoughtful queries that must be addressed around the classification of tumors.…”
Section: Funding Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…1 These are thoughtful queries that must be addressed around the classification of tumors. 1 These are thoughtful queries that must be addressed around the classification of tumors.…”
Section: Funding Supportmentioning
confidence: 99%
“…In fact, from the tumor sites shown by the authors in Table 1, 1 it is highly possible that tumors from other head and neck regions, instead of the nasopharynx, were included in their genome profiling. 1 In our opinion, the lack of accurate histological classification and evidence diminishes the clinical value of their findings regarding both major and rare NPC subtypes. 1 In fact, to the best of our knowledge, all 4 NPC wholeexome sequencing studies published from 2014 through 2017 3-6 consistently demonstrated that an IDH2 (or even isocitrate dehydrogenase 1, IDH1) mutation event is absolutely rare in NPC.…”
mentioning
confidence: 94%
See 3 more Smart Citations